2012
DOI: 10.1073/pnas.1118539109
|View full text |Cite
|
Sign up to set email alerts
|

Type II membrane protein CD69 regulates the formation of resting T-helper memory

Abstract: Memory T-helper (Th) lymphocytes are crucial for the maintenance of acquired immunity to eliminate infectious pathogens. We have previously demonstrated that most memory Th lymphocytes reside and rest on stromal niches of the bone marrow (BM). Little is known, however, regarding the molecular basis for the generation and maintenance of BM memory Th lymphocytes. Here we show that CD69-deficient effector CD4 T lymphocytes fail to relocate into and persist in the BM and therefore to differentiate into memory cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
124
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 37 publications
7
124
0
1
Order By: Relevance
“…Mice lacking CD103 show defects in establishing antigen‐experienced “tissue‐resident” T cells of peripheral tissues 162. For the establishment of bone marrow‐resident memory CD4 lymphocytes, we have shown that CD69 is essential 137. “Tissue‐resident” memory T cells have downregulated S1PR1, like CD69 + bone marrow memory T cells 33.…”
Section: “Tissue‐resident” Vs Bone Marrow‐resident Memory T Lymphocytesmentioning
confidence: 92%
See 3 more Smart Citations
“…Mice lacking CD103 show defects in establishing antigen‐experienced “tissue‐resident” T cells of peripheral tissues 162. For the establishment of bone marrow‐resident memory CD4 lymphocytes, we have shown that CD69 is essential 137. “Tissue‐resident” memory T cells have downregulated S1PR1, like CD69 + bone marrow memory T cells 33.…”
Section: “Tissue‐resident” Vs Bone Marrow‐resident Memory T Lymphocytesmentioning
confidence: 92%
“…Expression of CD69 is induced upon activation of T cells138 and therefore has been conceived as a marker of activation, also for bone marrow memory T cells 133, 139. However, in murine bone marrow, neither CD69 + nor CD69 − memory CD4 + T cells are cycling according to Ki‐67 expression 137. In human bone marrow, both CD69 + and CD69 − memory T cells have transcriptomes of quiescent cells, with very few genes differentially expressed between them.…”
Section: The Lifestyle Of Bone Marrow Memory T Lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Through CD69 targeting and deficiency experiments, Alari-Pahissa et al (2012) revealed that CD69 might have multiple immunoregulatory roles. CD69 has also been thought to play important roles in the generation and maintenance of professional memory Th lymphocytes (Shinoda et al, 2012). CD69 + T cells were demonstrated to induce indoleamine 2,3-dioxygenase in tumor-associated macrophages and hence to down-regulate inflammatory immune responses (Zhao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%